Protocolo de extracción de ADN para la detección de Brucella ovis en semen - Alvarez, Lucia Paula (2016)
Protocolo 1: Extracción con fenol/cloroformo: Adaptado de Matrone, M., Keid, L.B., Rocha, V.C., Vejarano, M.P., Ikuta, C.Y., Rodriguez, C.A., Ferreira, F., Dias, R.A., Ferreira Neto, J.S., 2009. Evaluation of DNA extraction protocols for Brucella abortus pcr detection in aborted fetuses or calves born from cows experimentally infected with strain 2308. Braz J Microbiol. 40, 480-489.